DESCRIPTION OF FORMER DRUGS AND ALCOHOL ABUSERS IN TETIRAH DHIKIR REHABILITATION CENTER YOGYAKARTA - Suhartini, Suhartini; Agni, Idha Arfianti Wira; Widagdo, Hendro (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Drugs and alcohol abuse is a major public health problem in worldwide. Prevalence of drug use in Yogyakarta, 2.72 percent of ages 10-59 (2.5371 million). Negative effect of drugs and alcohol abuse can produce crime behavior, even can cause death. The prevention, treatment, and rehabilitation in Indonesia have been done, but the basic characteristics of patients in rehabilitation centers have not been studied yet. The aim of the study was to determine the basic characteristics of former drugs and alcohol abusers in Tetirah Dhikir rehabilitation center Yogyakarta. This study was observational study, with total sampling methods. Observations, interview, and examination were performed on all patients. Case description was analyzed by descriptive statistics. All patients were men and productive age (34,4+1,35 years old). Mostly subjects unemployment (80%), totally recovered (60%), senior high school student (60%), outside Yogyakarta resident (60%), and up to 1 year followed therapy (60%). They preferred to choose multiple combination of alcohol (80%) and single kind of drug (60%). SGOT (25,2+8,2 U/L), SGPT (28,4+1,98 U/L), BUN (22,18+1,27 mg/dL), and creatinine (0,7+0,06 mg/dL) were within normal limit. The patients were mostly male, productive age, senior high school student, and unemployment, from outside Yogyakarta, totally recovered, and up to 1 year followed therapy. Mostly patients preferred to choose multiple combination alcohol and single kind of drug. The mean of liver and renal function test were within normal limit. Further evaluation of patients recovery status are needed
Keywords: rehabilitation center, former drug abuser, liver, renal function status